(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study is exploratory and pragmatic in nature and provides detailed insight of the functioning of solid waste management in Patna Municipal Corporation. Its looks into the functioning of PMC with respect to composition of labour force, Occupational related healthdisease and availability of public health facilities to workers. It lastly provides the recommendations and policy implications for solid waste management practices in PMC for further improvement. The lessons derived from PMC could be implemented in a larger context in India.